Reasons And Implications For Execluding International Terrorism Crimes From The Juridiction Of The International Criminal Court - Hayat, Houcine (Journal of Human Sciences, 2021)
The international community witnessed during the twentieth century and the beginning of the twenty-first century many incidents of international terrorism that have become a grave threat to security and international peace and friendly relations between nations and the breach of the system of collective international security, Besides the serious violation of human rights  Protected under international law, This risk was compounded when terrorism crimes in the world moved from automatic stage and unorganized operations to the field of organized crime that aims to achieve specific results according to progressive priorities and the ideological interaction of extremism with violence,Despite the gravity of international terrorism to international peace and security, it was not included in the substantive jurisdiction of the International Criminal Court.